Respuesta :

If f(x)=69-15x  then [tex]f(f^{-1}(x))=x[/tex]

Given :

[tex]f(x)=69-15x\\[/tex]

Lets find out [tex]f^{-1}(x)[/tex]. The steps to find out f inverse are

Replace f(x) by y

[tex]y=69-15x\\Interchange \; the \; variables\\x=69-15y\\solve \; for \; y\\x-69=-15y\\Divide \; by \; -15\\\frac{-x+69}{15} =y\\Replace \;y \;with \; f^{-1}\\f^{-1}=\frac{-x+69}{15}[/tex]

Now we find [tex]f(f^{-1}(x))[/tex]

Replace inverse function in the place of x in f(x)

[tex]f(f^{-1}(x))=f(\frac{-x+69}{15} )=69-15(\frac{-x+69}{15})=69-(-x+69)=69+x-69=x\\f(f^{-1}(x))=x[/tex]

Learn more :

brainly.com/question/11242094